Involvement of steroids in anti-inflammatory effects of PK11195 in a murine model of pleurisy. Issue 2 (2004) - da Silva, Marcelo Barreto Spillere; Farges, Roseli Coimbra; Fröde, Tânia Silvia
Abstract : BACKGROUND : Studies on peripheral benzodiazepine receptor function have yielded a diverse list of activities of which the anti-inflammatory effects need to be further examined. Aims : To evaluate the role of steroids, nitric oxide and adenosine-deaminase in the anti-inflammatory effect of PK11195. Methods : Pleurisy was induced by intrapleural injection of carrageenan in mice pre-treated or not with PK11195. Leukocytes, exudation, adenosine-deaminase (ADA) activity and nitric oxide (NO) level were measured. Steroid involvement was evaluated by pre-treatment with D, L-aminogluthetimide before PK11195. Results : Leukocytes, exudation and NO levels were reduced by PK11195 in the early (4 h) phase. In the late (48 h) phase, PK11195 decreased leukocytes and ADA activity. D, L-aminogluthetimide reversed the effect of PK11195 on exudate (4 h), as well as total and differential leukocytes and NO levels (48 h). Conclusions : Steroids, NO and ADA are implicated in the anti-inflammatory action of PK11195.